Security Control Strategy of Micro-grid Between Grid-connected and Off-grid Based on Virtual Synchronous Generator - Yizong GUO; Chuangxin GUO (发电技术)
As a major branch of integrated energy system, micro-grid is widely used in the local consumption of distributed generation. With the introduction of cold, heat and gas, the requirement of micro-grid security control is becoming higher and higher. The grid-connected and off-grid mode of micro-grid and the transition process between two operating states were analyzed, furthermore, a control strategy based on improved virtual synchronous generator (VSG) model was proposed. By using appropriate virtual impedance, the characteristics of synchronous reactance were effectively simulated, which ensured the stability of off-grid operation and makes the transition from grid-connected mode to off-grid mode smooth without adding additional control. An improved pre-synchronization control model was proposed for the switching from off-grid mode to grid-connected mode, which could accurately and quickly track the voltage amplitude, frequency and phase. Finally, the model was simulated in Matlab/Simulink environment with a practical example to verify the correctness and advantages of the proposed model.